2018
DOI: 10.1111/coa.13077
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation in relation to urgent suspicion of head and neck cancer referrals in Glasgow

Abstract: A link between deprivation and USOC referrals has been established. A difference in gender distribution between referrals and HNC was observed, more females are referred but a significantly higher number of patients with HNC are males. Neck lump is a very strong referral indicator for HNC and intermittent hoarseness is not. The findings from this analysis could be used to refine local referral patterns and priority of referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Additionally, a local review of head and neck cancer patients with respect to deprivation score has shown that more deprived patients present with more advanced disease. 12 This highlights the need for increased public education regarding the red flag symptoms, with the ultimate goal of early rather than late disease at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a local review of head and neck cancer patients with respect to deprivation score has shown that more deprived patients present with more advanced disease. 12 This highlights the need for increased public education regarding the red flag symptoms, with the ultimate goal of early rather than late disease at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in our department has shown that almost half of males with head and neck cancer live alone. 12 There are unique barriers to discharge from hospital in head and neck cancer cases. Managing tracheostomies and feeding tubes may pose a perceived challenge to relatively inexperienced healthcare staff and family members.…”
Section: Discussionmentioning
confidence: 99%
“…Referral patterns consistently show that more females are referred for cancer investigation, yet more males are diagnosed with head and neck cancer. 12 Most patients referred to clinic are in their sixth decade, with cancer occurring most frequently in the seventh decade.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis of ‘urgent suspicion of cancer’ referrals revealed that globus is frequently referred under the dysphagia category. 12 Currently, the non-red flag symptoms most commonly associated with patient concern are globus and pain in the neck area. Globus sensation tends to be referred as dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that socioeconomic status has not impacted upon the presence of laryngeal cancer in this study, a finding made in all cases of head and neck cancer urgent referrals. 13 As previously mentioned in the introduction, head and neck risk calculators are available, and are being updated. 3,4 This study does not purport to be any form of risk calculator but rather an in-depth analysis of hoarseness, the most frequent red flag symptom seen in otolaryngology clinic.…”
Section: Literature Comparisonmentioning
confidence: 99%